The Effects of Mycophenolate on the Formation of Granulation Tissue Post-operatively in Canine Tracheal Stent Patients (2014–2020) - Barber, Kevin F.; Loughin, Catherine A.; Marino, Dominic J.; Lesser, Martin (Frontiers in Veterinary Science, 2021)
Abstract Objectives: To determine if mycophenolate mofetil reduces the incidence and severity of granulation tissue in-growth in canine tracheal stent patients. Study design: Randomized clinical trial Animals: 111 dogs from the hospital population Methods: Client-owned dogs that received an endoluminal self-expanding tracheal stent for canine tracheal collapse between 2014-2020 were randomly assigned into one of two treatment groups. Control group medication protocol consisted of prednisone 0.5 mg/kg PO BID/SID/EOD x 30 days, hydrocodone 0.25 mg/kg PO TID x 30 days, cefovecin 8 mg/kg SQ post-placement. Mycophenolate group medication protocol was identical to the control with the addition of mycophenolate mofetil 10 mg/kg PO BID x 30 days, SID for life. Recheck tracheoscopy was performed at 1, 3, and 6 months post-stent placement. The presence and severity of granulation tissue were determined by tracheoscopy and were recorded as a percentage of tracheal lumen obstruction by blinded evaluators (none present, <25%, >25-50%, >50%). Results: At none of the three-time points was there a statistically significant difference in grade between controls and those receiving mycophenolate (p=0.467, p=0.330, and p=0.410,) respectively. Conclusions and Clinical Significance: Our results suggest that mycophenolate can be safely given to these patients, but do not support that its administration will reduce the incidence and severity of granulation tissue. Although a difference was observed in the severity of granulation tissue between the two groups, loss to follow-up may have influenced conclusions. A larger study would be warranted to further evaluate the effect of mycophenolate on the development of granulation tissue.